2013
DOI: 10.1007/s11136-013-0446-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in head and neck cancer patients after tumor therapy and subsequent rehabilitation: an exploratory study

Abstract: The results support the hypothesis that post-treatment maxillofacial rehabilitation in head and neck cancer does not only restore lost physical capabilities, but also brings about profound changes in patients' quality of life in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
7
22
0
4
Order By: Relevance
“…Eating difficulties, pain, fatigue, nausea and vomiting, and appetite loss were clinically relevant and statistically significant worse symptoms experienced among those with a post-operative weight loss [7] . Our results are in line with studies which report that approximately 3 months after esophagectomy, patients report worse functional aspects of QOL (physical, social, role and cognitive function) and more problems with fatigue, nausea and vomiting, pain, appetite loss, diarrhea, dry mouth and loss of taste than before treatment [5][6][7][8][9] . With the goal of improving postoperative outcomes, there has been a trend towards the increased use of trimodality therapy (induction chemotherapy and radiation therapy, followed by surgery) and minimally invasive esophagectomy (MIE) for esophageal resection; although their advantages and cost effectiveness remains debatable [10,11] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Eating difficulties, pain, fatigue, nausea and vomiting, and appetite loss were clinically relevant and statistically significant worse symptoms experienced among those with a post-operative weight loss [7] . Our results are in line with studies which report that approximately 3 months after esophagectomy, patients report worse functional aspects of QOL (physical, social, role and cognitive function) and more problems with fatigue, nausea and vomiting, pain, appetite loss, diarrhea, dry mouth and loss of taste than before treatment [5][6][7][8][9] . With the goal of improving postoperative outcomes, there has been a trend towards the increased use of trimodality therapy (induction chemotherapy and radiation therapy, followed by surgery) and minimally invasive esophagectomy (MIE) for esophageal resection; although their advantages and cost effectiveness remains debatable [10,11] .…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that in esophageal cancer, the quality of life rapidly deteriorates in most patients, due to disease-related symptoms such as dysphagia, pain, fatigue, appetite loss and constipation before treatment [5] . It has been documented that advances in surgical technique and post-operative care have considerably improved short come outcomes [6] . Eating difficulties, pain, fatigue, nausea and vomiting, and appetite loss were clinically relevant and statistically significant worse symptoms experienced among those with a post-operative weight loss [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Because of that, it is necessary to involve trained personnel not only before but also after HNC treatment [56].…”
Section: Quality Of Lifementioning
confidence: 99%
“…2) [7,9,12,13,17,18]. Показатели пациентки В. по данному опроснику выше или соответствуют верхней границе приведенных интервалов, что свидетельствует о более высоком уров-не качества жизни по каждой из функциональных шкал.…”
Section: результатыunclassified